"Globesity” An Outbreak: Asia - Prabhandhari, Ni Putu Dyana (Global and Policy Journal of International Relations, 2019)
ABSTRACTAs a phenomenon that brings change in various aspects of life, globalization has become one of the factors driving positive and negative changes in society. One of these changes is obesity which is a health problem in various regions, especially developing countries like Asia. Economic growth that occurs through foreign trade and investment, as well as technological developments, have had a devastating effect on the lifestyle of the world community, which increasingly relies on a small amount of its power while simultaneously consuming high amounts of calories. Lack of government regulation and public awareness related to public health increasingly facilitate the development of obesity in developing societies.Keywords: Obesity, Globalization, Economy, Health, Culture DOI : https://doi.org/10.33005/jgp.v7i02.1827